Adulticidal and post-exposure reproductive effects of crude n-hexane leaf extract of Ocimum suave Willd. on Anopheles gambiae s.l. - Esther Kadiene; Victor Enwemiwe; Eric Esiwo; Isaac Ighoyivwi; Ehimwenma Aghahowa; Precious Edhebe; Sarah Ifeta; Chioma Ojianwuna (Emerging Frontiers in Translational Biomedicine and Health Sciences, 2026)
Background: Insecticide resistance increases the need for complementary mosquito-control agents. This study evaluated the adulticidal and post-exposure reproductive effects of a crude n-hexane leaf extract of Ocimum suave Willd against field-derived Anopheles gambiae s.l. Methods: The extract was formulated in olive oil at nominal concentrations of 0.05%, 0.25%, 0.75%, 1.00%, 4.00% and 7.50% (v/v) and evaluated using the WHO tube-bioassay framework. Twenty-five non-blood-fed females aged 3-5 days were tested per tube, with four exposure replicates and two olive-oil controls per concentration. A parallel assay evaluated mosquitoes pre-exposed to 4% piperonyl butoxide (PBO). Results: Extract-only 24-h mortality increased from 24% at 0.05% to 70% at 7.50%, while PBO pre-exposure increased mortality to 56-91% across the corresponding concentrations. All 60-min knockdown values remained below 25%; therefore, KDT50 and KDT95 were not estimable within the observation period. Exposed females produced fewer eggs than control females (1.33 ± 0.44 versus 4.39 ± 0.74 eggs), and a negative-binomial model estimated an incidence-rate ratio of 0.304 (95% CI: 0.147-0.627; p = 0.0013). No hatching was recorded among eggs produced by exposed females. Conclusion: The concentration-related adult mortality, PBO-associated enhancement and model-supported post-exposure reproductive response support further chemical standardization and vector-control evaluation of O. suave crude leaf extract.